The Unfulfillable Promise of Meritocracy: Three Lessons and Their Implications for Justice in Education - Mijs, Jonathan J. B. (Social justice research, 2016)
This paper draws on a literature in sociology, psychology and economics that has extensively documented the unfulfilled promise of meritocracy in education. I argue that the lesson learned from this literature is threefold: (1) educational institutions in practice significantly distort the ideal meritocratic process; (2) opportunities for merit are themselves determined by non-meritocratic factors; (3) any definition of merit must favor some groups in society while putting others at a disadvantage. Taken together, these conclusions give reason to understand meritocracy not just as an unfulfilled promise, but as an unfulfillable promise. Having problematized meritocracy as an ideal worth striving for, I argue that the pervasiveness of meritocratic policies in education threatens to crowd out as principles of justice, need and equality. As such, it may pose a barrier rather than a route to equality of opportunity. Furthermore, meritocratic discourse legitimates societal inequalities as justly deserved such as when misfortune is understood as personal failure. The paper concludes by setting a research agenda that asks how citizens come to hold meritocratic beliefs; addresses the persistence of (unintended) meritocratic imperfections in schools; analyzes the construction of a legitimizing discourse in educational policy; and investigates how education selects and labels winners and losers.